2011
DOI: 10.1002/acr.20615
|View full text |Cite
|
Sign up to set email alerts
|

Associations of knee extensor strength and standing balance with physical function in knee osteoarthritis

Abstract: Objective. Knee extensor strength is an important correlate of physical function in patients with knee osteoarthritis; however, it remains unclear whether standing balance is also a correlate. The purpose of this study was to evaluate the cross-sectional associations of knee extensor strength, standing balance, and their interaction with physical function. Methods. One hundred four older adults with end-stage knee osteoarthritis awaiting a total knee replacement (mean ؎ SD age 67 ؎ 8 years) participated. Isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 51 publications
1
37
0
3
Order By: Relevance
“…The same five studies reported values for ML range (Collins et al, 2012;Hunt et al, 2009;Pua et al, 2011;Turcot et al, 2011;Vahtrik et al, 2014). Two studies reported on a DOF task, with one study finding an average range of 16.2 mm 22 , while the other reported a range of normalized values (see above) from 0.01 to 0.02 m −1 (Vahtrik et al, 2014).…”
Section: Anterior-posterior (Ap) and Medial-lateral (Ml) Rangementioning
confidence: 81%
See 3 more Smart Citations
“…The same five studies reported values for ML range (Collins et al, 2012;Hunt et al, 2009;Pua et al, 2011;Turcot et al, 2011;Vahtrik et al, 2014). Two studies reported on a DOF task, with one study finding an average range of 16.2 mm 22 , while the other reported a range of normalized values (see above) from 0.01 to 0.02 m −1 (Vahtrik et al, 2014).…”
Section: Anterior-posterior (Ap) and Medial-lateral (Ml) Rangementioning
confidence: 81%
“…Five studies reported values for AP range (Collins et al, 2012;Hunt et al, 2009;Pua et al, 2011;Turcot et al, 2011;Vahtrik et al, 2014). Of the five, three reported on SOF tasks with results ranging from 27.9 to 42.5 mm (Collins et al, 2012;Hunt et al, 2009;Turcot et al, 2011).…”
Section: Anterior-posterior (Ap) and Medial-lateral (Ml) Rangementioning
confidence: 92%
See 2 more Smart Citations
“…Studies have shown that the knee extensor strength correlates with walking speed and stair climbing performance in patients after total knee arthroplasty 25,26) . In particular, our earlier study suggested that the preoperative knee extensor strength on the affected side might be a good predictive factor of the future ambulatory status, such as the use of an assistive device in daily living 10) .…”
Section: Discussionmentioning
confidence: 99%